2012
DOI: 10.4314/ajpsy.v15i1.7
|View full text |Cite
|
Sign up to set email alerts
|

HIV sero-positivity in recently admitted and long-term psychiatric in-patients: prevalence and diagnostic profile

Abstract: Objective: Research on HIV in South Africa has not reflected the impact of the disease on psychiatric patients. The aims of the study were: to compare the HIV prevalence among patient groups in Weskoppies Hospital; to compare psychiatric diagnoses of infected and non-infected patients; to assess intravenous drug use and high-risk sexual behaviour; to establish HIV-syphilis association; and to investigate the rapid test performance for screening, compared to the confirmatory ELISA test. Method: Onehundred-and-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…The low proportion of injection drug users (3%) and SUD as a primary psychiatric diagnosis (7%), the absence of HIV infection in either group, and the lack of association between psychiatric diagnoses and prior hospitalization with HIV infection in our analysis reinforce this hypothesis, and provide evidence of high sexual risk for HIV among adults in psychiatric treatment in Brazil. Similar results have been found in India (Carey et al, 2007), South Africa (Henning, Krüger, & Fletcher, 2012), and Brazil (Wainberg et al, 2008), and they are consistent with the distribution of risk categories of reported AIDS cases in Brazil (68.7% and 15.5% are sexually or injection drug use related, respectively) (Brazil, Ministério da Saúde, 2011). Our findings are also consistent with prior studies in the USA (Carey, Carey, Maisto, Gordon, & Vanable, 2001; Cournos & McKinnon, 1997; Himelhoch et al, 2007; Prince et al, 2012; Rosenberg et al, 2001), with the exception of younger age at first sexual intercourse, a factor that has not been systematically addressed in prior studies.…”
Section: Discussionsupporting
confidence: 85%
“…The low proportion of injection drug users (3%) and SUD as a primary psychiatric diagnosis (7%), the absence of HIV infection in either group, and the lack of association between psychiatric diagnoses and prior hospitalization with HIV infection in our analysis reinforce this hypothesis, and provide evidence of high sexual risk for HIV among adults in psychiatric treatment in Brazil. Similar results have been found in India (Carey et al, 2007), South Africa (Henning, Krüger, & Fletcher, 2012), and Brazil (Wainberg et al, 2008), and they are consistent with the distribution of risk categories of reported AIDS cases in Brazil (68.7% and 15.5% are sexually or injection drug use related, respectively) (Brazil, Ministério da Saúde, 2011). Our findings are also consistent with prior studies in the USA (Carey, Carey, Maisto, Gordon, & Vanable, 2001; Cournos & McKinnon, 1997; Himelhoch et al, 2007; Prince et al, 2012; Rosenberg et al, 2001), with the exception of younger age at first sexual intercourse, a factor that has not been systematically addressed in prior studies.…”
Section: Discussionsupporting
confidence: 85%
“…In most previous studies from sub-Saharan Africa (but see [25]), no difference has been found in HIV prevalence between persons having different primary psychiatric disorders, i.e. schizophrenia, bipolar disorder, and depression [1-3,5], while several studies have reported high HIV prevalence in persons having ‘organic affective disorder’, ‘delirium’ [5], ‘psychotic disorder due to general medical condition’ [2] ‘and psychosis not otherwise specified’ [25], potentially due to inclusion of cases of SMI secondary to HIV into these categories. In the current study, we deemed the available chart diagnoses of HIV-associated mania/psychosis/depression unreliable, given the limited diagnostic modalities used at Butabika hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sexual risk behaviors such as having multiple sexual partners, engaging in unprotected sex, having sex in exchange for money and drugs, and having sex with prostitutes were found to be contributing to the high prevalence of HIV among this population [4,9]. The psychological problems that affect personal cognition, emotional regulation, and behavior are some of the reasons for this association [11].…”
Section: Introductionmentioning
confidence: 94%
“…The study thus aims to determine both the STI and HIV self-reported prevalence and sexual practices of mental health care users, and will contribute to the body of knowledge in developing comprehensive, inclusive, and integrated programmes for the MHCUs. Knowing the extent of the sexual risk and vulnerability of the MHCUs towards STI/HIV will alert the health care providers to effectively manage mental illness and HIV comorbidity among this population and improve their health [9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%